MINTHA-követés - Globalizációs problémák az önkormányzati fejlődés példáján - Horváth M., Tamás (Debreceni Jogi Műhely, 2005)
In Hungary almost every reform has its reference to the integration in the west, especially European Union. The explanation for failures is the difficulties of adjustment. The dilemma is what kind of reasons result this problem: is it a national feature or the original distress of Hungary. We can say that the root of it is the problem of following patterns. The origin of these patterns are from the western world but these patterns needed years or sometimes ages to reach the present situation. It was an organic development. In our modern world we can find plenty of legislative elements of globalization, unifying and harmonizing rules and institutions. Most of the international economic organizations make every effort to harmonize economic institutions, but the example of European Union shows that borders are not as simple as it seems. This harmonization and unification has to surpass it to a wider perspective (e.g. administration, public education, telecommunication or private law institutions, etc.). In the study I examine the development of self-governing and local governments. In Hungary over the last years – since the birth of self-governing – many changes could be found. Reforms followed reforms. According to a survey the most important fields of reforms are the following: decentralization privatization decreasing the role of public sector reform of the law for public servants information technology financial and budgetary management. Reforms of local governments are part of the globalization especially in those countries where change of the regime has happened. To reach the desired western pattern some lemmas are necessary: constitutional state territorialism of state guaranteed financial sources stability from the perspective of economy and policy. These foundational criterions are spread by international organizations like NAFTA, GATT, WTO, IMF, WB, OECD or EU itself. Plenty of recommendations exist on this field for administration and local governments. The Council of Europe has a basic document, the Charta of European Local Governments. If we examine the problem closer we can see that in spite of every recommendation or regulation, local governments are in trouble for example in Hungary. There are exact rules or principles to ensure the liberty or free space for them, but financial problems always exist. In the essay I analyzes the way of following patterns in typical countries and try to show how hard is to introduce a pattern from a moment to another that has prestigious past.